Asparaginyl endopeptidase promotes the invasion and metastasis of gastric cancer through modulating epithelial-to-mesenchymal transition - Cui, Yuehong (Oncotarget, 2016)
Asparaginyl endopeptidase (AEP) is a lysosomal protease often overexpressed in gastric cancer. AEP was expressed higher in peritoneal metastatic loci than in primary gastric cancer. Then we overexpressed AEP or knocked it down with a lentiviral vector in gastric cancer cell lines and detected the cell cycle arrest and the changes of the invasive and metastatic ability in vitro and in vivo. When AEP was knocked-down, the proliferative, invasive and metastatic capacity of gastric cancer cells were inhibited, and the population of sub-G1 cells increased. AEP knockdown led to significant decrease of expression of transcription factor Twist and the mesenchymal markers N-cadherin, ß-catenin and Vimentin and to increased expression of epithelial marker E-cadherin. These results showed that AEP could promote invasion and metastasis by modulating EMT. We used phosphorylation-specific antibody microarrays to investigate the mechanism how AEP promotes gastric cancer invasion and metastasis, and found that the phosphorylation level of AKT and MAPK signaling pathways was decreased significantly if AEP was knocked-down. Therefore, AKT and MAPK signaling pathways took part in the modulation.